2011
DOI: 10.1093/qjmed/hcr243
|View full text |Cite
|
Sign up to set email alerts
|

The statin-low cholesterol-cancer conundrum

Abstract: Статины являются одними из наиболее распространенных гиполипидемических препаратов в клинической практике. Целью данно го обзора было систематизировать наиболее частые побочные эффекты статинов, представив механизмы их развития, диагностику, тактику лечения и профилактику. По данным реестров и наблюдательных исследований частота развития статин-ассоциированных мышечных симптомов значительно выше, чем в рандомизированных контролируемых исследованиях. Диагностика клинических проявлений мышечных симптомов затрудн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 53 publications
4
62
0
1
Order By: Relevance
“…10). Although the relationship between the level of serum cholesterol and cancer mortality is controversial (51,52), our results implicate that inhibition of palmitoylated Src family kinases through cholesterol incorporation into Lyn-anchored membrane segments might be important for a novel cancer therapy.…”
Section: Discussionmentioning
confidence: 71%
“…10). Although the relationship between the level of serum cholesterol and cancer mortality is controversial (51,52), our results implicate that inhibition of palmitoylated Src family kinases through cholesterol incorporation into Lyn-anchored membrane segments might be important for a novel cancer therapy.…”
Section: Discussionmentioning
confidence: 71%
“…In many cohort studies (some from the 1980s) the cancer was inversely associated with CH measured 10-30 years earlier. The association persisted after exclusion of cancer cases appearing during the fi rst 4 years (16)(17)(18)(19)(20)(21)(22). Unfortunately, most of these studies have looked at the relationship only at one point in time.…”
Section: Is Low Cholesterol Associated With Cancer?mentioning
confidence: 99%
“…For instance, Newman and Hulley found that in almost all experiments on rodents both fibrates and statins produced cancer (Newman and Hulley, 1996), and at least nine cohort studies have found that cancer was inversely associated with cholesterol levels measured in healthy people from 10 to more than 30 years earlier (Ravnskov et al , 2012). Several cohort and case-control studies have also shown that cancer patients have used statin drugs significantly more often than control individuals of the same age and sex (Ravnskov et al , 2012).…”
mentioning
confidence: 99%
“…Several cohort and case-control studies have also shown that cancer patients have used statin drugs significantly more often than control individuals of the same age and sex (Ravnskov et al , 2012). The reason may be that LDL inactivates most types of microorganisms and their toxic products (Ravnskov and McCully, 2009;2012), and viral infections are the cause of almost 20% of all cancer types (Parkin, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation